Volumetric Interpretation of 3D Seismic Data from the Hillside IOCG Deposit in South Australia - Hossain, M.; Urosevic, Milovan; Kepic, Anton (EAGE, 2014)
A 3D high-resolution reflection seismic data were acquired to investigate its utilisation for exploration of typically excessively complex IOCG deposits in Hillside, South Australia. Full 3D pre-stack imaging produced results where seismic character well resembled different rock types. Further assessment of the value provided by seismic data required borehole calibration. Unfortunately only core samples were available. These information were enriched by utilising a specific gravity voxet that was extracted from the Rex supplied database. Core sample tests (velocity) and specific gravity information were utilised during the process of volumetric interpretation. We show that faults extracted from variance attribute correlate with the faults extracted using guided-tracking method. However, petrophysical data shows that the boundaries between gabbro and metasediments may not generate acoustic impedance contrast to be clearly detected by seismic reflection method. The tops to the main rock formations however are mappable in depth slices and agree very well with magnetic data. Further work involves correlation of seismic interpretation with the geological cross sections and lithological logs collected from the site.